Cultural identity in the ancient Mediterranean - Gruen, Erich S. (Getty Research Institute, 2011)
Ways of becoming Arcadian : Arcadian foundation myths in the Mediterranean / Tanja S. Scheer -- Pictorial foundation myths in Roman Asia Minor / Pascale Linant de Bellefonds -- Myths, images, and the typology of identities in early Greek art / Tonio Hölscher -- Herodotus and Persia / Erich S. Gruen -- Embracing ambiguity in the world of Athens and Persia / Margaret Cool Root -- "Manners makyth man" : diacritical drinking in Achaemenid Anatolia / Margaret C. Miller -- Keeping up with the Persians : between cultural identity and Persianization in the Achaemenid period / Maria Brosius -- The limits of Persianization : some reflections on cultural links in the Persian empire / Christopher Tuplin -- The pity of war : representations of Gauls and Germans in Roman art / I.M. Ferris -- Borealism : Caesar, Seneca, Tacitus, and the Roman discourse about the Germanic north / Christopher B. Krebs -- Ethnicity in Roman portraiture / Elizabeth Bartman -- Saving the barbarian / Greg Woolf -- Surviving by the book : the language of the Greek Bible and Jewish identity / Tessa Rajak -- Jewish identity at the limus : the earliest reception of the dura europos synagogue paintings / Steven Fine -- Keeping the dead in their place : mortuary practices and Jewish cultural identity in Roman North Africa / Karen B. Stern
Includes bibliographical references and index
Hier auch später erschienene, unveränderte Nachdrucke
Keywords: Mediterranean Region -- Civilization; Aufsatzsammlung; Ethnische Identität; Kulturelle Identität; Antike; Altertum; Mittelmeerraum